1981
DOI: 10.1128/aac.19.3.397
|View full text |Cite
|
Sign up to set email alerts
|

beta-Lactam resistance in Serratia marcescens: comparison of action of benzylpenicillin, Apalcillin, Cefazolin, and ceftizoxime

Abstract: The intrinsic mechanisms of resistance to beta-lactam antibiotics in Serratia marcescens IFO 12648 were investigated, comparing the action of benzylpenicillin, apalcillin, cefazolin, and ceftizoxime. The minimal inhibitory concentrations for this strain were 1,600, 3.13, 6,400, and 0.05 microgram/ml, respectively. The addition of ethylenediaminetetraacetic acid markedly reduced the minimal inhibitory concentrations of benzylpenicillin and cefazolin, whereas those of apalcillin and ceftizoxime were not influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Table 3 summarizes data with nonenteric gram-negative bacilli and streptococci. Apalcillin was significantly more active than piperacillin against P. aeruginosa (MIC90s, 8.0 versus 64 ,ug/ml; MIC50s, 2.0 versus 4.0 pLg/ml) and against Acinetobacter calcoaceticus subsp. anitratus (MIC90s, 8.0 versus 64 ,ug/ml; MIC50s, 2.0 versus 16 ,ug/ml).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 summarizes data with nonenteric gram-negative bacilli and streptococci. Apalcillin was significantly more active than piperacillin against P. aeruginosa (MIC90s, 8.0 versus 64 ,ug/ml; MIC50s, 2.0 versus 4.0 pLg/ml) and against Acinetobacter calcoaceticus subsp. anitratus (MIC90s, 8.0 versus 64 ,ug/ml; MIC50s, 2.0 versus 16 ,ug/ml).…”
mentioning
confidence: 99%
“…Apalcillin was significantly more active than piperacillin against P. aeruginosa (MIC90s, 8.0 versus 64 ,ug/ml; MIC50s, 2.0 versus 4.0 pLg/ml) and against Acinetobacter calcoaceticus subsp. anitratus (MIC90s, 8.0 versus 64 ,ug/ml; MIC50s, 2.0 versus 16 ,ug/ml). Among the P. aeruginosa isolates, 11.5% were resistant to carbenicillin (MIC, >128 ,ug/ml), 5.3% were resistant to piperacillin (MIC, >64 ,ug/ml), and only 0.7% were resistant to apalcillin (MIC, >64 ,uglml).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftizoxime is slightly less active than cefotaxime against S. aureus, with an MIC90 of 6.3 lLg/ml compared to 3.1 lLg/ml. Ceftizoxime has been more active than cefotaxime against highly resistant Serratia marcesc ens, with MICs two-to eightfold lower (83). In contrast, there has been minimal or no difference in the activity of ceftizoxime and cefotaxime against the streptococcal species (79,(80)(81)(82)84).…”
Section: In Vitro Activitymentioning
confidence: 99%
“…Examination of clinically isolated S. marcescens strains revealed that most of them possess fimbriae capable of adherence to the human uroepithelial cells and considered to be a colonization factor in the urinary tract infections [ 20 ]. S. marcescens is resistant to many antibiotics traditionally used to eradicate bacterial infections, including β -lactams and aminoglycosides [ 21 , 22 ]. Its motility and ability to form flagellated swarmer cells as well as the biofilm formation are important virulence/pathogenicity factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%